Perlindungan Hak Terhadap Tenaga Kerja Wanita Dalam Perspektif Hukum - Sidqi, Faris Ali (Media Hukum Indonesia (MHI), 2024)
The purpose of this study is to determine the protection of rights for female workers from the perspective of national law and international law. The scope of this study focuses on the realm of labor law and international law. The research methods used are normative research, conceptual approach and legislative approach. Data collection techniques are carried out by tracing primary data and secondary data. The results of this study are: In the realm of national law, there are rights for female workers that are specifically regulated in Law Number 13 of 2003 concerning Manpower, as follows: a. Working Hours for Female Workers; b. Provision of Maternity and Miscarriage Leave; c. Provision of Time for Breastfeeding During Working Hours; d. Provision of Rest Period on the First and Second Days of Menstruation; and e. Prohibition on Termination of Employment (PHK) for Female Workers. The policy related to the rights granted to female workers was previously reaffirmed in Article 84 that the use of rest time rights as regulated in the law does not affect wages. And in the realm of international law. In 1948 the UN approved resolution 217A/III relating to the Universal Declaration of Human Rights or UDHR, considered as the basis for upholding the rights and principles of equality, security, integrity, and dignity of every individual. Then the Convention on the Elimination of All Forms of Discrimination Against Women or CEDAW was ratified. In 2004 the Indonesian Government signed the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families.